Determining Primary Care Physician Information Needs to Inform Ambulatory Visit Note Display - Clarke, M.A.; Steege, L.M.; Moore, J.L.; Koopman, R.J.; Belden, J.L.; Kim, M.S. (Applied Clinical Informatics, 2014)
Citation: Erratum to: Clarke MA, Steege LM, Moore JL, Koopman RJ, Belden JL, Kim MS. Determining primary care physician information needs to inform ambulatory visit note display. Appl Clin Inf 2014; 5: 190e http://dx.doi.org/10.4338/ACI-2013-08-RA-0064e